2015
DOI: 10.1001/jamapediatrics.2015.1475
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Child Poverty, Brain Development, and Academic Achievement

Abstract: IMPORTANCE Children living in poverty generally perform poorly in school, with markedly lower standardized test scores and lower educational attainment. The longer children live in poverty, the greater their academic deficits. These patterns persist to adulthood, contributing to lifetime-reduced occupational attainment.OBJECTIVE To determine whether atypical patterns of structural brain development mediate the relationship between household poverty and impaired academic performance. DESIGN, SETTING, AND PARTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
580
6
32

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 792 publications
(657 citation statements)
references
References 34 publications
39
580
6
32
Order By: Relevance
“…A small study of 58 adolescents by John Gabrieli's group at the Massachusetts Institute of Technology, published in April, was the first to relate cortical volume to scores on state tests of math and reading (12). A paper published by Pollak and colleagues in July that analyzed MRI scans of 398 children and young adults between ages 4 and 22 reported that after adjustment for other factors, structural brain differences explained 20% of the testing gap between poor kids and middle class or well-off students (13). One value of tying brain measures to outcomes is that it opens the door for them to be used as biomarkers, or surrogate endpoints that could help determine whether an intervention is working, Gabrieli notes.…”
Section: Complex Implicationsmentioning
confidence: 99%
“…A small study of 58 adolescents by John Gabrieli's group at the Massachusetts Institute of Technology, published in April, was the first to relate cortical volume to scores on state tests of math and reading (12). A paper published by Pollak and colleagues in July that analyzed MRI scans of 398 children and young adults between ages 4 and 22 reported that after adjustment for other factors, structural brain differences explained 20% of the testing gap between poor kids and middle class or well-off students (13). One value of tying brain measures to outcomes is that it opens the door for them to be used as biomarkers, or surrogate endpoints that could help determine whether an intervention is working, Gabrieli notes.…”
Section: Complex Implicationsmentioning
confidence: 99%
“…La parte más anterior del lóbulo frontal, se divide a su vez en las áreas dorsolateral, orbitofrontal y medial, las cuales están conectadas con diversas estructuras subcorticales, formando circuitos frontosubcorticales (Stuss & Knight, 2013). Dado que desde el punto de vista del neurodesarrollo, el lóbulo frontal es una de las últimas áreas en madurar (completando su formación hacia la segunda década de vida), es de esperar que sea una de las estructuras más afectadas luego de un evento traumático en los niños y adolescentes (Hair, Hanson, Wolfe, & Pollak, 2015).…”
Section: Uno De Los Mayores Cambios Introducidos En La Quinta Versiónunclassified
“…53 Given the close nexus between poverty and undernutrition, it is not surprising that significant correlations between poverty and brain development have been demonstrated. 54,55 Other research looking at factors associated with neurodevelopment and poverty has focused on the toxic effects of violence, abuse, and exposure to conflict. Data from the recent Lancet series on early child development 56 also suggest that by using conjoint estimates of poverty and stunting, some 200 million children worldwide are at risk for suboptimal development with huge economic costs over their lifetimes and potentially across generations.…”
Section: The Impact Of Nutrition On Neurodevelopmentmentioning
confidence: 99%